Nowe media - perspektywy badawcze (Świat Idei i Polityki, 2010)
The term “new media” should be considered in accordance to the temporal and spatial context, because something “new” could be “new” only now and here or would be “new” only someday and somewhere, and not forever and everywhere. Therefore it is necessary to take into consideration that hundreds years ago the press was “new”, in the 20th Century the radio and television became “new media”, and today the term “new media” means, above all, the Internet, mobile telephones and other digital media. Nevertheless, R.D. Wimmer and J.R. Dominick describe the term “new media” in broader context, taking into consideration also different implications of the ICT to the human and social life. There are many different aspects of the “new media” that need to be investigated, and many of them are subjects of many studies realized by scientists from different countries. They research the impact of the “new media” to the traditional mass media, the influence of the Internet on politics and the political marketing, but also other social, economical and communicational aspects of this complex phenomenon. It is important also that the “new media” are useful tools for the researchers on every stage of any scientific investigation. There is strong need to investigate the “new media” in different contexts to understand better the new modern reality.